The evolutionarily conserved long non‐coding RNA LINC00261 drives neuroendocrine prostate cancer proliferation and metastasis via distinct nuclear and cytoplasmic mechanisms. Issue 7 (26th April 2021) - Mather, Rebecca L.; Parolia, Abhijit; Carson, Sandra E.; Venalainen, Erik; Roig‐Carles, David; Jaber, Mustapha; Chu, Shih‐Chun; Alborelli, Ilaria; Wu, Rebecca; Lin, Dong; Nabavi, Noushin; Jachetti, Elena; et al.
Abstract : Metastatic neuroendocrine prostate cancer (NEPC) is a highly aggressive disease, whose incidence is rising. Long noncoding RNAs (lncRNAs) represent a large family of disease‐ and tissue‐specific transcripts, most of which are still functionally uncharacterized. Thus, we set out to identify the highly conserved lncRNAs that play a central role in NEPC pathogenesis. To this end, we performed transcriptomic analyses of donor‐matched patient‐derived xenograft models (PDXs) with immunohistologic features of prostate adenocarcinoma (AR + /PSA + ) or NEPC (AR − /SYN + /CHGA + ) and through differential expression analyses identified lncRNAs that were upregulated upon neuroendocrine transdifferentiation. These genes were prioritized for functional assessment based on the level of conservation in vertebrates. Here, LINC00261 emerged as the top gene with over 3229‐fold upregulation in NEPC. Consistently, LINC00261 expression was significantly upregulated in NEPC specimens in multiple patient cohorts. Knockdown of LINC00261 in PC‐3 cells dramatically attenuated its proliferative and metastatic abilities, which are explained by parallel downregulation of CBX2 and FOXA2 through distinct molecular mechanisms. In the cell cytoplasm, LINC00261 binds to and sequesters miR‐8485 from targeting the CBX2 mRNA, while inside the nucleus, LINC00261 functions as a transcriptional scaffold to induce SMAD‐driven expression of the FOXA2 gene. For the first time, these results demonstrate hyperactivation of the LINC00261‐ CBX2‐FOXA2 axes in NEPC to drive proliferation and metastasis, and that LINC00261 may be utilized as a therapeutic target and a biomarker for this incurable disease. Abstract : Neuroendocrine prostate cancer (NEPC) is a highly aggressive disease with high incidence of metastasis. Here, we identified LINC00261 among the top upregulated transcripts in NEPC. Inside the nucleus, LINC00261 promoted anchorage‐independent growth and metastatic gene programs by recruiting the SMAD2/3 transcriptional machinery to FOXA2 cis ‐regulatory elements. Cytoplasmic LINC00261 blocked the binding of miR‐8485 to CBX2 and induced a CBX2‐driven proliferative gene program. Our study demonstrates the role of LINC00261 ‐CBX2‐FOXA2 axis in proliferation and metastasis of NEPC.